The Influence of Social Media Marketing, Customer Experience and Online Delivery Service on Customer Satisfaction at Kedai Janji Jiwa Johor Medan Branch - Andini Putri Lestari; Rifky Budi Setiawan; Mesra B (Cattleya Darmaya Fortuna, 2026)
This study aims to determine the effect of Social Media Marketing, Consumer Experience, and Online Delivery Service on Customer Satisfaction. This study uses a quantitative method with an associative approach. Data were collected through questionnaires and analyzed using multiple linear regression tests with the help of SPSS. The results of the study indicate that partially Social Media Marketing has a positive and significant effect on Customer Satisfaction with a significance value of 0.009 <0.05. Meanwhile, Consumer Experience and Online Delivery Service do not have a significant effect on Customer Satisfaction. Simultaneously, the three independent variables have a significant effect on Customer Satisfaction with a significance value of 0.029 <0.05. The R Square value of 0.597 indicates that the independent variables are able to explain Customer Satisfaction by 59.7%.